2004
DOI: 10.1093/molehr/gah120
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of genes involved in innate immunity: association with preterm delivery

Abstract: An altered inflammatory activity due to functionally relevant polymorphisms of the innate immune system may influence pathways leading to labour and, therefore, impact on the frequency of preterm birth. We examined five polymorphisms of the innate immune system in a large cohort of preterm very-low-birth-weight (VLBW, n = 909) and term-born infants (n = 491) and their mothers (n = 747). The primary outcome was preterm versus term birth. Frequencies of polymorphisms in mothers of term-born infants versus mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 31 publications
5
51
1
3
Order By: Relevance
“…In addition and as expected, both TLR4 polymorphisms are in total linkage disequilibrium (D 0 ¼ 1.000). In fact, cosegregation among these two mutations has also been largely stated [13,30,31].…”
Section: Resultsmentioning
confidence: 98%
“…In addition and as expected, both TLR4 polymorphisms are in total linkage disequilibrium (D 0 ¼ 1.000). In fact, cosegregation among these two mutations has also been largely stated [13,30,31].…”
Section: Resultsmentioning
confidence: 98%
“…For these reasons, IL-6 is considered a "marker" of high risk status for PTB (Romero et al 1993). In addition, genetic association studies demonstrated that a single nucleotide polymorphism (SNP) in the promoter region of the IL6 gene (C-174G) decreases promoter activity, and the (G/G) homozygote associates with increased risk of PTB (Hartel et al 2004). IL6, as well as the gene encoding its receptor (IL-6 receptor IL6R), through which IL-6 mediates its biological function, are therefore strong candidates for PTB and perhaps for the ethnic disparity in PTB.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore in modern obstetric practice, oxytocin is widely used to induce and augment contractions during labor [28]. Furthermore, associations between several maternal gene polymorphisms, such as tumor necrosis factor, interleukin (IL)-4, IL-1ß receptor antagonist, matrix metalloproteinase 9, ß2-adrenergic receptor, vascular endothelial growth factor and for Factor V Leiden [11] and PTB have been described. Consequently, we speculated that OXTR gene polymorphisms might also play a role in PTB and to the best of our knowledge are the first to have investigated association of OXTR single nucleotide polymorphisms rs2254298, rs53576, rs2228485, rs237911 and PTB.…”
Section: Discussionmentioning
confidence: 99%